Improving uptake of vaccines in pregnancy: A service evaluation of an antenatal vaccination clinic at a tertiary hospital in the UK. (February 2022) - Ralph, Kate MI; Dorey, Robert B; Rowe, Rebecca; Jones, Christine E
Abstract: Background: Vaccination against pertussis and seasonal influenza is recommended for all pregnant women in the UK. More recently COVID-19 vaccination has also been offered to women in pregnancy. Objectives: To evaluate the uptake of vaccines in pregnant women within a midwife-led immunisation clinic and to assess factors influencing pregnant women's decisions about accepting vaccination. Methods: Uptake of vaccines amongst pregnant women referred to a single UK centre for antenatal care between 01/01/19 and 02/10/19 was assessed. Interviews with 20 pregnant women explored views of antenatal vaccination and experiences of the vaccination service. Findings: Amongst 4420 women, uptake was 90.6% for pertussis and 78.8% for influenza vaccines. Factors influencing vaccine-related decision-making amongst 20 interviewed women were: healthcare professional recommendation, perceived susceptibility and risk of infection, and previous experience of vaccination and vaccine-preventable disease. Conclusions and Implications for Practice: Uptake of pertussis and influenza vaccines within a secondary care immunisation service was higher than the national or regional average. The model of vaccine delivery was associated with high levels of satisfaction. This model of vaccine delivery could be implemented elsewhere to increase vaccine uptake, and should be considered for delivery of COVID-19 vaccines in the future.